2015
DOI: 10.1186/s12889-015-2611-7
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding is associated with waist-to-height ratio in young adults

Abstract: BackgroundThe current study investigated the association between breastfeeding and adult weight distribution using an emerging indicator of weight distribution, the waist-to-height ratio (WHtR).MethodsThe study sample consisted of two subsamples of individuals that were part of the National Longitudinal Study of Adolescent Health. One sample (n = 1 179) consisted of individuals from the sibling pair data. A second sample (n = 4 648) consisted of individuals that were not part of the paired data. Regression mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Our findings contribute to the small body of literature using sibling-pair designs to test risk factors for obesity across the life course. Within-family studies examining the association between breastfeeding and obesity have been conducted across the largest number of cohorts, with three studies finding that breastfeeding was protective 23,26,27 and four studies finding no effect. 21,22,24,25 While the recent review by Albers et al, 30 which combined data from five studies, and one more recent study, 31 concluded that smoking during pregnancy increased risk for obesity, we found no evidence of associations between prenatal smoking and childhood obesity at age 2 or 5.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings contribute to the small body of literature using sibling-pair designs to test risk factors for obesity across the life course. Within-family studies examining the association between breastfeeding and obesity have been conducted across the largest number of cohorts, with three studies finding that breastfeeding was protective 23,26,27 and four studies finding no effect. 21,22,24,25 While the recent review by Albers et al, 30 which combined data from five studies, and one more recent study, 31 concluded that smoking during pregnancy increased risk for obesity, we found no evidence of associations between prenatal smoking and childhood obesity at age 2 or 5.…”
Section: Discussionmentioning
confidence: 99%
“…In research across all risk factors, some studies used fixed effects models, [21][22][23]33,39 while others compared betweenfamily and within-family estimates. [24][25][26][27][28]31,32,40 We previously used the Linked CENTURY Study to examine the relationship between cesarean delivery and BMI z-scores at 5 years of age by decomposing the total association into In the breastfeeding analysis, there were 1006 sibling sets (2260 individuals), in which there was variability in childhood obesity. In the cesarean delivery analysis, there were 1008 sibling sets (2263 individuals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Birth-related factors consisted of birth weight (overweight: ≥4 kg, non-overweight: <4 kg) [12], gestational age (≥42 weeks, <42 weeks) [19], and whether or not the child was breastfed (yes or no) [20]. …”
Section: Methodsmentioning
confidence: 99%
“…Thirty articles, published between 2003 and 2019, were identified that met the inclusion criteria and examined ever, compared with never, consuming human milk and overweight and/or obesity. [1][2][3][4][5][6][7][8][9][10][11][14][15][16][17][19][20][21][22]26,27,[30][31][32][35][36][37][39][40][41] They presented evidence from 21 independent studies. Four of the 21 studies were also described in the section about evidence from siblings (i.e., Linked CENTURY Study, Children of NLSY79, Add Health, and CDS).…”
Section: Child Development Supplement Of the Panel Study Of Income Dynamics (Cds)mentioning
confidence: 99%